Semen charcteristics and histological changes in testes of saanen crossbred bucks fed palm kernel cake - based diets - Sidik, Siti Aisyah (2013)
An experiment was conducted to evaluate the effects of different diets based on PKC on sperm quality and spermatogenesis of goats. Fifteen adult Saanen crosses buck were randomly assigned into three formulated diet which are concentrates (Control),65% Palm Kernel Cake (PKC), 65% Palm Kernel Cake plus ammonium molybdate and sodium sulphate (PKCMS) for six months. Semen characteristics and body weight (BW) were determined fortnightly and dry matter intake (DMI) was measured daily. Blood serums from each buck were collected for copper and testosterone concentration. Testes samples of three bucks from each dietary treatment were assessed for Cu concentration, quantitative histological evaluation and transmission electron microscopy (TEM) viewing. There were no differences in initial and final BW among treatments (P> 0.05). The average daily gain (ADG) were highest (P0.05) in the Control diet followed by PKC and PKCMS groups. The DMI values were not significantly different (P>0.05) among dietary treatment groups. There are no interaction between treatment and time of semen collections. Sperm concentrations and total sperm motility percentage showed significant differences (P<0.05) among dietary treatments. The sperm concentration of PKC was 4% and 16% higher compared to Control and PKCMS, respectively. Total percentage of motility of sperm was consistent with the sperm concentration (P<0.05). Addition of molybdenum sulphate with PKC did not alter the semen quality. However, PKCMS showed the highest mean number among treatment in the percentage of abnormalities (P<0.05). Progressive motility percentage was significantly higher in PKC and Control as compared to PKCMS. Rapid motility was affected by PKC and significantly higher than Control and PKCMS respectively (P<0.05). Other motility parameters as follows sperm motion parameters, VAP, VSL, VCL, ALH, BCF, STR, and LIN did not differ significantly (P>0.05) between dietary treatment groups. Generally, the best semen quality in Saanen crossbred buck was obtained in PKC group. Mean testosterone values under PKC group were significantly higher than PKCMS and Control group at week 4 and 24 (P <0.05). In histological evaluation, there were no significant different (P>0.05) in the mean number of spermatogonia, spermatocyte, spermatid, spermatozoa,Sertoli cells, Leydig cells. However, degenerative cells were significantly higher in goat fed with PKC compared to others (P<0.05). This condition is reflected in the TEM result when there was significant increase in the number of degenerated cell ofthe same animal group. Toxic effect on mitotic secondary permatocytes and cap phase spermatids were observed in buck fed on PKC. In conclusion, the Cu content in PKC diet did not alter the overall spermatogenic cells in buck after feeding for six months. However, TEM evaluation did showed the effect of Cu content in PKC in seminiferous tubules. Further study with larger number of buck and longer period are required.